Pengetahuan Mahasiswa Mengenai Isu Keamanan Sekuriti pada Pusat Data Nasional : Ransomware: Sebuah Studi Pra dan Pasca Webinar di Dua Perguruan Tinggi - Latifah Iriani; Rakhmat Prasetyo Agung; Joko Supriyanto; Andi Sugandi; Muhammad Immawan Aulia (Journal of Cyber Health and Computer, 2025)
The National Data Center (PDN) plays a critical role in storing and managing government and public data, positioning it as a strategic target for cybersecurity threats such as ransomware. This study aims to assess university students’ knowledge of PDN security issues, with a specific focus on ransomware attacks, before and after attending a structured webinar series. A pre-test and post-test design was implemented involving students from Universitas Siber Muhammadiyah and Universitas Islam Mulia Yogyakarta. The results revealed a significant improvement in students’ understanding of cybersecurity issues following the webinars. Key contributing factors included educational background, frequency of technology use, and active participation during discussions. The findings suggest that webinars are an effective educational tool to enhance cybersecurity literacy among students. The study recommends integrating cybersecurity awareness into the academic curriculum and conducting more webinars to address the growing complexity of digital security threats.